ASSESSMENT OF THE LEVEL OF ANXIETY AS AN INDICATOR OF REGULATORY-ADAPTIVE CAPABILITIES OF STUDENTS TO EDUCATIONAL LOAD IN HIGHER EDUCATIONAL INSTITUTION - Julia V. Kashina , Iulia V. Gluzman , Maxim A. Vaskov , Alexander A. Bulavkin , Olga S. Melikova , Natalya Kh. Gafiatulina (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this publication is to clarify the level of anxiety as an indicator of the regulatory-adaptive capabilities of students to the educational load in a higher educational institution. The Spielberger-Khanin method was used as a methodological tool for the study. The regulatory-adaptive status was determined depending on the level of personal and reactive anxiety of students, and measurements were made at the beginning and at the end of the academic year. At the end of the academic year, the regulatory-adaptive capabilities of students to the academic load decreased, which led to an increase in the level of anxiety and to the redistribution of students in groups according to the level of anxiety